Democracy, Governance and Decentralization - Allan ROSENBAUM (Revista Transilvană de Ştiinţe Administrative, 2000)
In the half century that has followed the conclusion of World War II there has been increasing concern about issues of democratization and good governance. This concern was given an initial impetus by the growing belief in the aftermath of World War II that democratic governments were both less likely to seriously violate basic human rights as well as to resort to violence and war as a means of resolving disputes between themselves.